ISOLASI BAKTERI PENGHASIL ASAM INDOL ASETAT (AIA) DAN PENGARUHNYA TERHADAP VIABILITAS BENIH CABAI MERAH - Albert Sembiring; Natalia Lusianingsih Sumanto (Universitas Muhammadiyah Mataram, 2021)
Plant growth-promoting rhizobacteria are names that contribute directly or indirectly to plant growth. This group of bacteria will stimulate plant growth through the synthesis of phytohormones (bio-stimulant). Indole acetic acid (IAA) plant endogenous auxin is one of the phytohormone type that these bacteria can generate. IAA has functions for root elongation, cell division and plant growth and development differentiation. This research aims to obtain possible isolates that can generate IAA to optimize the viability of germinating red pepper seed. Bacteria have been isolated by serial dilution spread of Nutrient agar medium was incubation over a 24-hour period at 28oC (room temperature). The amount of IAA was measured by spectrophotometric analysis, selected isolate on the basis of the results, used to encourage the germination of red pepper seed. Ten out of sixteen bacterial isolates could produce IAA in the range of 7.96 ppm - 47.23 ppm. The RC 3 isolate produced the highest IAA while the RC 12 was the other way round. The isolate chosen using this experiment showed an increase in the viability of red pepper seed compare seed germination to 33%, growth spontaneity 37%, vigor index 10%, growth rates 6% and max. growth 13%. IAA isolates could therefore increase the viability of red pepper and got potential of a biofertilizer component.